The Disunity of the Ummah Become 73 Groups in Takhrij Al-Hadith Perspective - Abdul Rohman; Mulyani Mudis Taruna (Matan : Journal of Islam and Muslim Society, 2020)
A Hadith states that Muslims will disunity into 73 groups. When the Prophet was still alive all the problems of the Ummah could be returned to him, so there was no disunity. But after he died, many problems surfaced. The event of tahkim (arbitration) as an attempt to resolve the Shiffin war, instead gave rise to three major groups, namely the Shi’ite, Khawarij and Muawwiyah. The last group is often referred to as the ahlus Sunni. These events are often used as legal points, for the emergence of various religious groups in Islam today. The writing of this study uses the study literature method. As for the results of this study concluded, that: a) The Hadith concerning "The disunity of the people into 73 groups", included the famous Hadith (popular), the Hadith that has been widely delivered by many figures and the general public also knows it; b) The narrators on each path or sanad traversed by the mukharrij al Hadith, on thobaqat tabi'in namely Abi Salamah with a friend named Abu Hurairah unknown meeting, so the position of this Hadith is not up to the degree of saheeh, because it is not continued (ghoiru muttasil). Based on the Quran, Hadith, or ushul analysis, the Hadith about the disunity of Muslims into 73 groups, it is better not to be used as the main material in lectures and or sermons, because it brings more damage than the benefit.